Estudio del sistema de iluminación en el laboratorio de productos lácteos de la Universidad Técnica de Cotopaxi, para la prevención del riesgo físico - Reatiqui Caillagua, Jefferson Paúl (2017)
The project on the lighting system of the dairy laboratory of the Technical University of Cotopaxi aims to minimize the visual risks of both students and teachers of the institution, which is caused by the lack or excess of illumination. By characterizing the dairy laboratory, the following results were obtained. With the realization of the measurements through the calculation by crews or grids and the luxometer, to know the amount of luxes with which the laboratory consists, when determining the measure of 340 luxes that is the current measurement of the laboratory, the same one that does not Complies with the provisions of the regulations on risks, calculations were made the appropriate conclusions of the laboratory. A new distribution of luminaires is proposed, in accordance with the current regulations of the Ecuadorian Occupational Safety and Health Standard and Executive Decree 2393 for dairy laboratories. As a conclusion it is necessary to take corrective actions such as a new distribution and increase of nine luminaires reaching to obtain a lighting of 525.65 luxes that allow the visual comfort in the students and teachers of the institution of higher education.